2005
DOI: 10.1177/004051750507500307
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Fiber and Fabric Uses and the Factors Contributing to Military Clothing Comfort and Satisfaction

Abstract: Attitudes of military consumers toward commercial and military fibers, fabrics, and military battle dress uniforms (BDU) are assessed using item-by-use appropriateness scaling and conjoint analysis. The item-by use appropriateness ratings uncover strong stereotypes about the tactile and functional characteristics of the fibers/fabrics and their appropriateness for use in specific situations and/or environmental circumstances. Both the fibers and fabrics and their uses and characteristics are reduced to a minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Through the use of this model, further research has identified four main clothing and equipment aspects which influence perceived comfort [15][16][17][18]:…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of this model, further research has identified four main clothing and equipment aspects which influence perceived comfort [15][16][17][18]:…”
Section: Introductionmentioning
confidence: 99%
“…Such judgement is vague and complex and involves multidimensional factors (Li, 2001;Wong et al, 2002). Thermal properties are more important for the comfort of hot weather clothing than that of temperate weather (Schutz et al, 2005). Thermal-moisture sensation is commonly associated with sultry, damp, clammy, clingy, hot, cold and non-absorbent (Li, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have documented the importance of fabric thickness and flexibility (Tremblay-Lutter et al 1996), absorption (Barker 2002) and fibre content (Hogge et al 1988) to wearer comfort in a variety of garment types. Research has established the importance of fit in achieving comfort for gloves (Tremblay-Lutter et al 1996), sports apparel (Wheat and Dickson 1999, Chae 2002, Turk 2002, coveralls ), men's apparel (Hogge et al 1988) and military battle dress uniforms (Schutz et al 2005).…”
Section: Clothing Comfortmentioning
confidence: 99%